PENETAPAN WALI HAKIM DALAM PERKAWINAN (Studi Di KUA Karanganyar Kabupaten Karanganyar) - Sasmito, Seno Aris; Sari, Adinda Dewi Mutiara (LPPM STAI Muhammadiyah Probolinggo, 2023)
Residents assume the absence of a guardian can switch to anyone without regard to the rules. Meanwhile, the practice in the KUA area of Karanganyar District in the selection of guardians is carried out based on the order of marriage guardians. The execution of marriage uses a guardian judge if the guardian is a non-muslim, the guardian of the nasab is unknown (mafqud), the child of a mother and runs out of the guardian of the nasab. In appointing a guardian the judge is not necessarily to the head of the KUA, but rather gives precedence to the wali aqrab to the wali ab'ad. This is done in order to preserve the honor of the parents who take care of him. Even so, the transfer of the guardian of the nasab to the guardian of the judge already has provisions, therefore the purpose of this article is to find out the determination of the guardian of the judge in the marriage and the role of the guardian of the judge in the implementation of the marriage. The primary data source is the result of interviews with the Head of KUA and 9 married couples, supported by secondary data. The result of his research is that the determination of the guardian of the judge is carried out based on the consideration of the applicable law in Indonesia. The Office of Religious Affairs determines a marriage in terms of Islamic law and positive law. It's just that it's related to the reason that the guardians of most guardians of judges apply positive law. Therefore, the legal basis used in determining marriage is KHI and PERMA RI Number 30 of 2005.